Effectiveness of Relaxation Handheld Fingertechnique and Benson Relaxation to the Changes Level of Post Operative Pain Sectio Caesarea in Rsi Sakinah Mojokerto - Windartik, Emyk; Yuniarti, Enny Virda; Akbar, Amar (International Journal of Scientific Research and Management (IJSRM), 2017)
Pain after major or minor surgery will impact the anatomical and physiological changes in patients. Givinganesthetic is not always sufficient to eliminate the sensation of pain because the pain response of eachpatient is different. Postoperative pain caesarea section must be solved with non-pharmacological methodsof handheld eg relaxation techniques and relaxation benson finger. The purpose of this research was toprove efektikitas between both these relaxation techniques to changes in the level of postoperative painsection caesarea in RSI Sakinah Mojokerto. The researh design is pre experiment with methods of the twogroups without pretest-posttest control group. The population in the researh of 20 respondents with nonprobabilitysampling technique that was concecutive sampling, while the samples are 10 respondents in therelaxation group and 10 respondents handheld finger on relaksai group benson. Analysis of data usingunivariate analysis showed a decrease in pain level respondents in the relaxation group handheld finger 10respondents (100%), while the decrease in the level of pain in the relaxation group benson much as 8respondents (80%). Wilcoxon statistical test results showed ρ = 0.005